Triple-Network Symbiosis: How AI Enables Cross-Domain Collaboration Among Business, Finance, and Cybersecurity (2022-2026) - Ku, Fei (International Journal of Multidisciplinary Research, 2026)
Artificial intelligence (AI) has reshaped the interaction paradigm between digital commerce, finance, and cybersecurity, forming a mutually dependent triple-network symbiosis: the value network (creating and distributing cross-domain economic value), the responsibility network (allocating risk and compliance obligations), and the governance network (establishing rules for cross-domain interaction). This review synthesizes 7 key studies (2022-2026) to unpack the operational logic of each network and their interdependent relationships: the value network is driven by AI-enabled resource integration (e.g., multi-tenant infrastructure, LSTM prediction); the responsibility network is anchored by AI-powered risk sharing (e.g., privacy-enhancing technologies, multi-agent risk balancing); the governance network is guaranteed by AI-aided rule making (e.g., modular compliance frameworks, incentive systems). Findings reveal that: the three networks are mutually reinforcing—value creation requires responsibility allocation to mitigate risks, and governance rules constrain and guide both value distribution and responsibility sharing; SMEs are the critical nodes connecting the triple networks; and modular AI architectures and privacy technologies are the core enablers of network symbiosis. This framework provides a new perspective on cross-domain AI collaboration, offering guidance for researchers, practitioners, and policymakers to build sustainable and inclusive cross-sector ecosystems.